Logistics System Development to Support the Growth of Logistics Industry Business - Noiraj, Jomnongjai; Shoommuangpak, Porntip (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2020)
The objective of this research is to study the logistics system development to support the growth of logistics industry business by analyzing data both qualitatively and quantitatively. In carrying out this research, the researcher surveyed quantitative data from interviews with 500 business executive using descriptive statistics, reference statistics and plural statistics. The results showed that logistics system development to support the growth of logistics industry business with the highest mean. In relation to customer relationship management, such as providing knowledge on customer logistics in the form of training in resource management, including recruiting professional executives in logistics to increase management potential in the area of data management, for example, using the enterprise resource planning (ERP) system to store the logistic information for efficiency. & technological innovations, such as accepting payments & making payments via the internet such as mobile money transfers etc. For the hypothesis testing found that large industrial businesses & small & medium businesses Giving priority to logistics system development to support the growth of logistics industry business. There was no significant difference at .05 level. The analysis results of the developed structural equation model show that passing the assessment criteria, consistent with the empirical data the probability level of chi-square is .078. The relative chi-squared value is 1.192. The consistency index is .969 & the root index of the mean square of the error estimation equals. .020.